Membangun Resiliensi Pada Anak Usia Dini Melalui Intervensi - Jusnita; 2Syahrul Safutra; Hartina (Jurnal Euforia, 2025)
Resilience is an individual's ability to survive, adapt, and bounce back when faced with stress or adversity. In early childhood, resilience forms an important foundation for social-emotional development and readiness to face future challenges. However, not all children naturally possess optimal levels of resilience, necessitating planned interventions tailored to the developmental characteristics of early childhood. This study aims to comprehensively examine efforts to build resilience in early childhood through structured interventions. The research method used was a literature review, reviewing various scientific sources, including national and international journals, reference books, and relevant research reports. The study results indicate that interventions focused on strengthening emotional regulation, positive relationships with the environment, and developing social skills significantly contribute to increasing children's resilience. Interventions that are carried out consistently, involve educators and parents, and use a playful approach have proven effective in fostering resilience in early childhood. Thus, structured interventions can be an effective strategy in supporting the development of resilience in children from an early age